Evaluation of MRI-based synthetic CT for lumbar degenerative disease: a comparison with CT - Ziwei Jiang; Yuhang Zhu; Wei Wang; Zongbao Li; Yunxi Li; Mengchao Zhang (Scientific Reports)
Abstract Patients with lumbar degenerative disease typically undergo preoperative MRI combined with CT scans, but this approach introduces additional ionizing radiation and examination costs. To compare the effectiveness of MRI-based synthetic CT (sCT) in displaying lumbar degenerative changes, using CT as the gold standard. This prospective study was conducted between June 2021 and September 2023. Adult patients suspected of lumbar degenerative disease were enrolled and underwent both lumbar MRI and CT scans on the same day. The MRI images were processed using a deep learning-based image synthesis method (BoneMRI) to generate sCT images. Two radiologists independently assessed and measured the display and length of osteophytes, the presence of annular calcifications, and the CT values (HU) of L1 vertebrae on both sCT and CT images. The consistency between CT and sCT in terms of imaging results was evaluated using equivalence statistical tests. The display performance of sCT images generated from MRI scans by different manufacturers and field strengths was also compared. A total of 105 participants were included (54 males and 51 females, aged 19–95 years). sCT demonstrated statistical equivalence to CT in displaying osteophytes and annular calcifications but showed poorer performance in detecting osteoporosis. The display effectiveness of sCT images synthesized from MRI scans obtained using different imaging equipment was consistent. sCT demonstrated comparable effectiveness to CT in geometric measurements of lumbar degenerative changes. However, sCT cannot independently detect osteoporosis. When combined with conventional MRI’s soft tissue information, sCT offers a promising possibility for radiation-free diagnosis and preoperative planning.